Context- and Subgroup-Specific Language Changes in Individuals Who Develop PTSD After Trauma - Todorov, German; Mayilvahanan, Karthikeyan; Cain, Christopher; Cunha, Catarina (Frontiers in Psychology, 2020)
Post-traumatic Stress Disorder (PTSD) is a very common condition with more than 3 million new cases per year in the US alone. The right diagnosis in a timely manner is key to ensuring a prompt treatment that could lead to a full recovery. Unfortunately, avoidance of trauma reminders, social stigma, self-presentation, and self-assessment biases often prevent individuals from seeking timely evaluation, leading to delays in treatment and suboptimal outcomes. Previous studies show that various mental health conditions are associated with distinct patterns of language use. Analyzing language use may also help to avoid response bias in self-reports. In this study, we analyze text data from online forum users, showing that language use differences between PTSD sufferers and controls. In all groups of PTSD sufferers, the usage of singular first-person pronouns was higher and that of plural first-person pronouns was lower than in control groups. However, the analysis of other word categories suggests that subgroups of people with the same mental health disorder (here PTSD) may have salient differences in their language use, particularly in word usage frequencies. Additionally, we show that word usage patterns may vary depending on the type of the text analyzed. Nevertheless, more studies will be needed to increase precision by further examine a variety of text types and different comorbidities. If properly developed, such tools may facilitate earlier PTSD diagnosis, leading to timely support and treatment, which are associated with better outcomes.